Ameliorative effects of TiO2 nanoparticles and sodium nitroprusside on seed germination and seedling growth of wheat under PEG-stimulated drought stress - Faraji,Javad (2019)
Abstract: Seed germination and early seedling growth are sensitive to drought stress in wheat. A factorial experiment was arranged based on a completely randomized design with three replicates to study the impacts of TiO2 nanoparticles (TiO2 NPs: 0, 500, 1000 and 2000 mg.L) and sodium nitroprusside (SNP: 0 and 100 μM), as NO donor, on seed germination and seedling growth of wheat under polyethylene glycol (PEG)-induced drought stress (0, -0.4 and -0.8 MPa). Our results revealed that PEG-stimulated drought stress significantly decreased germination percentage (GP), germination energy (GE), germination rate (GR), root length (RL), shoot length (SL), root fresh weight (RFW), shoot fresh weight (SFW) and vigor index (VI) but increased mean germination time (MGT) in wheat seeds. However, application of TiO2 NPs and SNP alone or in combination significantly enhanced GP, GE, GR, RL, SL, RFW, SFW and VI up to 23.72%, 50%, 33.74%, 85.38%, 93.28%, 73%, 91.91% and 91.04% respectively, but significantly reduced MGT up to 28.36% under severe drought stress. Our results showed that application of TiO2 NPs and SNP alone or in combination can significantly alleviate the adverse effects of PEG-stimulated drought stress on seed germination and early seedling growth of wheat.